# Find the value of x in the equation 2(x - 3) + 5x = 5(2x + 6).

**Solution:**

It is given that

2(x - 3) + 5x = 5(2x + 6)

Using the multiplicative distributive property

2x - 6 + 5x = 10x + 30

Transposing the like terms on LHS and constant terms on the RHS

2x + 5x - 10x = 30 + 6

By further calculation

- 3x = 36

Divide both sides by -3

x = -12

Therefore, the value of x is -12.

## Find the value of x in the equation 2(x - 3) + 5x = 5(2x + 6).** **

**Summary:**

The value of x in the equation 2(x - 3) + 5x = 5(2x + 6) is -12